Crypto Economy and International Law : Determining the Regulatory and Private Law Rules Governing the Blockchain - Lehmann, Matthias, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
The blockchain is the world's first truly global mechanism for the transfer and storage of value. The distribution of its nodes all around the world and the resulting 'omniterritorial' nature of the blockchain create enormous challenges for the law. This book discusses the technological and philosophical underpinnings of the new crypto phenomena. It describes the varying approaches of regulators of different states to capture these phenomena with traditional or new rules. It also addresses the difficulties in determining the applicable private law, in particular the property rules governing virtual assets. The book showcases the conflicts, issues and problems that result from overlapping national rules and suggests avenues for their solution.